Managing the performance of non-family employees: a case study of a China-based family-SME. Issue 2 (4th May 2019) - Haslan, Risky Harisa; Ramos, Hazel Melanie L.; Mustafa, Michael
ABSTRACT: Family-SMEs utilize their non-family employees to achieve their developmental goals and aspirations. A particular challenge facing many Family-SMEs is how to effectively manage and motivate their non-family employees. Performance management systems represents an important means through which Family-SMEs can achieve this. The limited empirical evidence on performance management systems in Family-SMEs suggest that they are largely ad-hoc in nature and biased towards family-members. Drawing on organizational justice theory, this study seeks to explore how Family-SMEs performance manage their non-family employees, and non-family employees' reactions to such process. Based on an illustrative case study, we found that Family-SMEs utilized both informal and formal practices to manage their non-family employees' performance. Moreover, we also identified how family involvement in management can heighten a sense of injustice concerning the process among non-family employees'. Our findings make a valuable contribution to the existing but limited literature on the performance management of non-family employee.